Prinsip-Prinsip Ekonomi Syari’ah - Abdullah AF; Abd Wahab; Rahmawati Rahmawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The purpose of this study is to describe and analyze the experience of the system adopted by the Indonesian state having two economic policies. The research method is library (Library research). Source data (primary) in the form of books relating to Islamic thought models and complementary (secondary) data to interpret source data in the form of magazines, newspapers relating to the title to be discussed. The results of this study discuss Islamic Economics; the existence of Islamic economic principles in Indonesia which are based on five universal values namely; The principles of monotheism, Adl, Nubuwwah, Khilafah and Ma'ad and the existence of Islamic economic law are the Principle of Representative (Khalifah), The Principle of Amar Ma'ruf Nahy Munkar, Amar Ma'ruf , The Principle of Tazkiyah, tazkiyah , The Principle of Falah, is the concept of success human beings., The Principle of Honesty and Truth, this principle is reflected in every transaction that must be firm, clear, and certain both the goods and the price.